Communication in critical embedded systems : first Workshop, WoCCES 2013, Brasília, Brazil, May, 10, 2013, second Workshop, WoCCES 2014, Florianópolis, Brazil, May 9, 2014, third Workshop, WoCCES 2015, Vitória, Brazil, May 22, 2015, 4th Workshop, WoCCES 2016, Salvador, Brazil, June 3, 2016, Revised selected papers /: first Workshop, WoCCES 2013, Brasília, Brazil, May, 10, 2013, second Workshop, WoCCES 2014, Florianópolis, Brazil, May 9, 2014, third Workshop, WoCCES 2015, Vitória, Brazil, May 22, 2015, 4th Workshop, WoCCES 2016, Salvador, Brazil, June 3, 2016, Revised selected papers. (2017) - Unknown
No abstract available